Research Trends in Emerging Contaminants on the Aquatic Environments of Tanzania - H. Miraji; O. C. Othman; F. N. Ngassapa; E. W. Mureithi (Scientifica)
The continuity for discovery and production of new chemicals, allied products, and uses has currently resulted into generation of recent form of contaminants known as Emerging Contaminants (ECs). Once in the aquatic environment ECs are carcinogenic and cause other threats to both human’s and animals’ health. Due to their effects this study was aimed at investigating research trends of ECs in Tanzania. Findings revealed that USA and EU countries were leading in ECs researches, little followed by Asia, South Africa, and then Zambia. Only few guidelines from USA-EPA, WHO, Canada, and Australia existed. Neither published guidelines nor regulations for ECs existed in Tanzania; rather only the occurrence of some disinfection by-products and antibiotics was, respectively, reported in Arusha and Dar es Salaam, Tanzania. As these reports had a limited coverage of ECs, henceforth, these findings constitute the first-line reference materials for ECs research in Tanzania which shall be useful for future monitoring and regulation planning.